THE INFLUENCE OF PARTICIPATORY LEADERSHIP STYLE, THE AVAILABILITY OF HUMAN RESOURCES AND INFORMATION TECHNOLOGY ABILITY ON WORK MOTIVATION WHICH IMPACT EMPLOYEE PERFORMANCE AT THE DISTRICT LEVEL IN PANGKALPINANG CITY - Wan, Tjik; Sugianto, Efendi; Hamdan, Hamdan; Juhari, Juhari (PT. Hafasy Dwi Nawasena, 2025)
The improvement of public sector employee performance depends greatly on various managerial and technological factors. This study aims to analyze the influence of participative leadership style, human resource availability, and information technology capability on work motivation and their impact on employee performance at the sub-district level in Pangkal Pinang City. A quantitative approach was employed using a survey method involving 75 respondents. The data were analyzed using Structural Equation Modeling (SEM) with the Partial Least Squares (PLS) technique through SmartPLS version 4. The results indicated that participative leadership style, human resource availability, and information technology capability significantly influenced work motivation. Work motivation was also found to have a direct effect on employee performance. Meanwhile, the direct effects of participative leadership style and information technology capability on performance were not significant; however, both exerted indirect effects through work motivation as a mediating variable. These findings highlight the critical role of work motivation in mediating the influence of managerial and technological factors on achieving optimal employee performance in the public sector